Nuclear Magnetic Resonance-Based Approaches for the Structural and Quantitative Analysis of Mycotoxins - Yun Hwan Kim; Seon Yeong Lee; Jin Young Kim; Hyojin Cho; Hyang Sook Chun; Sangdoo Ahn (Magnetochemistry)
Mycotoxins are toxic secondary metabolites produced by various fungal species, posing significant food safety concerns due to their health impacts and economic burden. Accurate structural elucidation and quantitative analysis are essential for effective risk assessment and regulatory control. This review highlights recent advances in the application of nuclear magnetic resonance (NMR) spectroscopy for the structural and quantitative analysis of major mycotoxins, including aflatoxins, ochratoxins, fumonisins, trichothecenes, and zearalenone. One- and two-dimensional NMR techniques enable precise molecular characterization, positional isomer identification, including modified forms such as masked or conjugated mycotoxins, and toxicity-related molecular interaction investigation. NMR spectroscopy offers superior structural resolution, high reproducibility, and nondestructive analysis, making it invaluable in mycotoxin research. Quantitative NMR spectroscopy has emerged as a robust and accurate method for determining the absolute concentration and purity of mycotoxins, without requiring analyte-specific reference standards, an advantage particularly important for modified toxins lacking commercially available standards. The integration of NMR-based approaches strengthens analytical reliability, supports reference material development, and contributes to enhanced food safety assessment. This review also discusses ongoing analytical challenges and future directions, including the application of artificial intelligence to improve the automation and interpretation of NMR data in mycotoxin research.